Information technology and communication as reference practices in knowledge management: A systematic review of the literature (2016)
The objective of this review is to identify reference practices supported by Information and Communication Technologies, which encourage the implementation of Knowledge Management within organizations. Based on the Systematic Review Methodology, this research project consisted in three phases: the research protocol development;the collection and analysis of information retrieved from the Social Sciences Citation Index (SSCI) of the Institute for Scientific Information (ISI); and finally, the results generation. This study indicates that management practices related with applications and tools, databases, communities of practice, frameworks and networks, promote good outcomes in knowledge management process when applied in real context.